(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The study made assessment of power outage and small and medium enterprise operations in Ikot Ekpnene metropolis. The research design for this study is a survey design. The population of the study consisted of all the operators and managers of SMEs in the study area. Simple random sampling technique was used to select 120 respondents out of the population. The instrument used for data collection was questionnaire. The instrument was validated by two experts in Test and Measurement. Data from completed questionnaires was subjected to simple percentage analysis and presented in figures. The findings showed and concluded that the power crisis in Ikot Ekpene metropolis have forced middle size enterprises to implement solutions to feed and protect their electronic assets, whenever the local power supplier fails to deliver. Blackouts are constant in our country, and continuously cause equipment failures and operations delay. The study recommends that PHCN should establish a scheme of helping small-scale entrepreneurs when it comes to power supply. PHCN should at least provide exception for the area in order to assist them in reaching their goals rather than being part of the power rational scheme as of other non-business areas. For business owners, there should be plans of settling special electricity backup plan either for single business or as a group to reduce overall costs involved. Basing on the current growth of technology, electric supply are widely available form different area hence with proper effort and willingness SMEs can manage to establish their own backup source to avoid the associated effects and challenges that are brought about by power fluctuations